1983
DOI: 10.2307/3897938
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Differences between Basin and Wyoming Big Sagebrush in Contiguous Populations

Abstract: Basin and Wyoming big sagebrush plants growing in contiguous populations were studied to identify potential habitat differences in plant water and soil relationships. At 3 study sites, basin big sagebrush plants were growing in and adjacent to a drainage, while Wyoming big sagebrush plants occupied areas adjacent to the basin big sagebrush populations. Soil-and leaf-water potentials and leaf-transpiration resistances were measured from May to October 1980 to identify differences between basin and Wyoming big s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 4 publications
1
24
1
Order By: Relevance
“…Other studies have also reported that soil characteristics affected species composition in the Artemisia steppe (Anderson, 1956;Barker and McKell, 1983;Jensen et al, 1990;Lentz and Simonson, 1987a, b;Passey et al, 1982;Shumar and Anderson, 1986;Swanson et al, 1986). Similar to our findings, several studies reported that soil texture (Jensen et al, 1990;Shumar and Anderson, 1986;Swanson et al, 1986) and soil nitrogen (Barker and McKell, 1983;Jensen et al, 1990) influenced plant species composition in the Artemisia steppe. Unlike our study, these previous efforts did not report total soil carbon or depth to a Bt horizon as associated with plant species composition.…”
Section: Plant Compositionsupporting
confidence: 89%
See 2 more Smart Citations
“…Other studies have also reported that soil characteristics affected species composition in the Artemisia steppe (Anderson, 1956;Barker and McKell, 1983;Jensen et al, 1990;Lentz and Simonson, 1987a, b;Passey et al, 1982;Shumar and Anderson, 1986;Swanson et al, 1986). Similar to our findings, several studies reported that soil texture (Jensen et al, 1990;Shumar and Anderson, 1986;Swanson et al, 1986) and soil nitrogen (Barker and McKell, 1983;Jensen et al, 1990) influenced plant species composition in the Artemisia steppe. Unlike our study, these previous efforts did not report total soil carbon or depth to a Bt horizon as associated with plant species composition.…”
Section: Plant Compositionsupporting
confidence: 89%
“…Also in contrast to our results, previous studies reported that numerous other soil characteristics were associated with variation in plant species composition. However, the discrepancies in findings are due to previous studies investigating the influence of soil factors on only dominant species (Anderson, 1956;Barker and McKell, 1983;Jensen et al, 1990;Lentz and Simonson, 1987a, b;Passey et al, 1982;Shumar and Anderson, 1986;Swanson et al, 1986), whereas our research investigated soil factors influence on community composition. Slope was the only non-soil factor we found to be at least moderately correlated with plant species composition.…”
Section: Plant Compositioncontrasting
confidence: 72%
See 1 more Smart Citation
“…texture, depth to clay layers and total depth), microtopography (i.e. concave, convex) and incident radiation (a function of slope and aspect) vary across space and influence the spatial heterogeneity of vegetation (West et al 1978;Passey et al 1982;Barker and McKell 1983;Jensen et al 1990;Johnson and Miller 2006;Davies et al 2007). These drivers can vary at fine spatial scales (tens to thousands of hectares), and so fire regimes likely varied at similarly fine scales across sagebrush-steppe and juniper woodlands in the Intermountain West, as they have in other more mesic forested plant communities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Management objectives also need to be tailored to the individual subspecies of the big sagebrush complex because of differing environmental characteristics influencing vegetation structure and composition, varying responses to grazing and other disturbances, and differing resistance to weed invasion (Beetle and Young 1965;Morris et al 1976;Winward and Tisdale 1977;Hironaka 1978;McArthur and Plummer 1978;Blaisdell et al 1982;Barker and McKell 1983).…”
Section: Introductionmentioning
confidence: 99%